Gender and sexuality in Asian American literature. - Wong, Sau-ling C.; Santa Ana, Jeffrey J. (Signs: Journal of Women in Culture & Society)
Focuses on gender and sexuality in Asian American literature. Developments in Asian American cultural criticisms; Description of Asian American political and sexual objectification; Analysis of the role of Asian women in Asian American history.